Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If we have a function $f:X\rightarrow Y$ where $A\subset X$, is it true to say that $f^{-1}(f(A))=A$?

share|cite|improve this question
$f^{-1}(f(A)) \supseteq A$ , link – pedja Nov 2 '11 at 7:52
up vote 8 down vote accepted

As noted, the asserted equality is not true.

In general, one inclusion always holds: $$A\subseteq f^{-1}(f(A)).$$

How to see that? Remember that $x\in f^{-1}(B)$ if and only if $f(x)\in B$.

Now, to show $A$ is contained in $f^{-1}\Bigl( f(A)\Bigr)$, let $a\in A$; we need to show that $a\in f^{-1}\Bigl( f(A)\Bigr)$. But this holds if and only if $f(a)\in f(A)$, which holds since $a\in A$ and $f(A) = \{f(x)\mid x\in A\}$.

The other inclusion does not hold in general, but you do have the following:

Proposition. Let $f\colon X\to Y$ be a function. Then $f$ is one to one (injective) if and only if for every $A\subseteq X$, we have $A=f^{-1}(f(A))$.

Proof. Assume first that $f$ is injective, and let $A\subseteq X$. We already know that $A\subseteq f^{-1}(f(A))$, so we only need to show that $f^{-1}(f(A))\subseteq A$. Let $x\in f^{-1}(f(A))$; we want to prove that $x\in A$. That means that $f(x)\in f(A)$, so there exists $a\in A$ such that $f(x)=f(a)$. But since $f$ is one-to-one, this implies $x=a$, so $x\in A$, as desired.

Conversely, assume that for every $A\subseteq X$, $A=f^{-1}(f(A))$. Let $x,x\in X$ be such that $f(x)=f(x')$. We need to show that $x=x'$. Let $A=\{x\}$; then $f(x')\in f(A)$, so $x'\in f^{-1}(f(A))$. By assumption, $f^{-1}(f(A))=A=\{x\}$, so we can conclude that $x'\in \{x\}$; but this means $x'=x$, which is what we needed to prove. $\Box$

share|cite|improve this answer

No. Not in general. Note that if you take the constant map $x\mapsto 1$ mapping $\mathbb{R}\to\mathbb{R}$ then $f^{-1}(f(\{0\}))=\mathbb{R}$. In fact, the equality you wrote holds true for all subsets of $X$ precisely when $f$ is injective.

share|cite|improve this answer

No. This need not be true.

For example, $X=Y=\{0,1\}$, $f(x)=0$ and $A=\{1\}$.

$f(A) = \{0\}$ and $f^{-1}(\{0\})=X$, so $f^{-1}(f(A))=X\neq A$.

share|cite|improve this answer
I think you have some typos here, but I don't want to edit your work. – Squirtle Sep 10 '12 at 15:12
@dustanalysis: Why do you think I have typos here? – Asaf Karagila Sep 10 '12 at 15:26
Why do you use f(x), do you mean f(X)? – Squirtle Sep 10 '12 at 15:28
@dustanalysis: No, but it would be the same thing. When I write that $f(x)=0$ it is a defining property, it means that for every $x\in\operatorname{dom}(f)$ we have that $f(x)=0$. – Asaf Karagila Sep 10 '12 at 15:31

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.